Dosing vancomycin in the super obese: less is more. (6th September 2018) - Crass, Ryan L; Dunn, Ryan; Hong, Joseph; Krop, Lynne C; Pai, Manjunath P
Abstract: Background: Vancomycin remains the mainstay of empirical therapy directed against MRSA. National guidelines recommend empirical dosing based on total body weight with trough-level therapeutic drug monitoring (TDM), which may not be optimal in obese and super obese patients. Furthermore, nomograms for empirical vancomycin dosing by estimated kidney function pre-date standardization of creatinine assays. Objectives: To determine an empirical vancomycin dosing strategy for obese and super obese adults that is consistent with the AUC monitoring paradigm. Methods: We conducted a population pharmacokinetic study using data obtained from routine peak and trough TDM of vancomycin in obese and super obese adults. An empirical dosing nomogram was developed using Monte Carlo simulation to identify vancomycin doses that optimize the probability of efficacy and minimize the probability of acute kidney injury based on AUC. Results: A total of 346 patients were included encompassing a wide range of body weight (69.6–293.6 kg) and BMI (30.1–85.7 kg/m 2 ) values. In the final model, vancomycin clearance (CLV ) was described using a linear combination of age, serum creatinine, sex and allometrically scaled body weight. Monte Carlo simulation demonstrated that maintenance doses >4500 mg/day were not required to achieve pharmacodynamic AUC targets in obese and super obese patients at clinically relevant values of CLV . Conclusions: Empirical vancomycin dosing informed by common clinical variables, including standardized creatinine, with subsequent individualization using AUC-targeted TDM can optimize therapy in obese and super obese adults.